Free land programs revisited: A case study of four Kansas communities - Bauer, Karl Francis (Kansas State University, 2018)
Over the past century, the mechanization of agriculture, the rise of the automobile, youth out-migration, and a variety of other factors have led to the population and economic decline of once-booming small towns across rural America, and especially the Great Plains. As a result, schools, churches, and services have been forced to close or consolidate; in many cases, entire towns have vanished. A variety of state and federal mitigation practices have been put forward, often to no avail or limited success. This has caused some communities to take matters into their own hands, including the initiation of land giveaways — programs in which an applicant receives a residential lot on which they are required to build a house to designated specifications and live in it for a given number of years. In Kansas alone, 27 communities have employed such a program, and in most other Great Plains states and provinces, at least one community has done the same. The programs were initially a media curiosity, and major news outlets, including USA Today, made small towns across Kansas famous by featuring them on the front page of their publications. Some of the most recent scholarly literature, published in 2007, pointed to “impressive” results in reversing a century-old trend. That was over a decade ago, however, and more recent news publications have been more pessimistic. This research is based on interviews and conversations with five program directors and local decisionmakers, four new residents, and a newspaper editor in the communities of Marquette, Ellsworth, Mankato, and Lincoln, Kansas, to determine what has changed in these communities, what makes some programs more successful than others, what challenges the programs have faced, and whether locals think the programs are a success. These programs have not reversed the 100-year-old trend of rural decline, but, in some communities, they have caused small population and construction booms bringing new money into the community and have delayed the closing or downsizing of community institutions. In short, the programs have proven to be a short-term solution to a long-term problem.
Keywords: Free land; Rural; Population; Decline; Kansas; Economic development